PELAKSANAAN HAK PEMBEBASAN BERSYARAT NARAPIDANA DILEMBAGA PEMASYARAKATAN PEREMPUAN KELAS IIB PADANG MENURUT UNDANG-UNDANG NO. 22 TAHUN 2022 TENTANG PEMASYARAKATAN - Gessia Ferandha, Marisa Jemmy dan (Normative Jurnal Ilmiah Hukum, 2024)
Granting conditional release is a form of implementing the rights of prisoners who are serving a criminal term in a correctional institution in accordance with Law Number 22 of 2022 in Articles 9 and 10 concerning Corrections. The granting of conditional release is aimed at prisoners who behave well while serving their sentence in a correctional institution. In terms of the implementation of granting parole, it has not run optimally at the Class IIB Padang Women's Correctional Institution, there are several prisoners who have not received their right, namely parole, due to several obstacles, namely delays in completing administrative requirements. , the absence of a guarantor by the prisoner. The formulation of the problem in this paper is first, how are the rights of conditional prisoners implemented according to Law Number 22 of 2022 concerning Corrections in the Class IIB Padang Women's Correctional Institution, secondly, what obstacles do the Class IIB Padang Women's Correctional Institution face? in implementing the right to parole according to Law Number 22 of 2022 concerning Corrections and how to overcome obstacles to implementing the rights of conditional prisoners in Correctional Institutions according to Law Number 22 of 2022 concerning Corrections in the Padang Class IIB Women's Correctional Institution. The method in this research is an empirical juridical approach which is descriptive. Data collection techniques are through interviews and literature studies, then processed through editing, coding and tabulation processes and analyzed qualitatively. The results of this research indicate that the implementation of the right to parole for prisoners by the Class IIB Padang Women's Prison is considered not completely successful, as can be seen from the comparison of data on parole in the Class IIB Padang Women's Prison. Prisons for the 2021-2022 period between those proposed and those realized have not been fully met with the proposed amount. Obstacles faced in implementing the right to parole for prisoners in the Class IIB Padang Women's Prison for the 2021-2022 period include procedures for applying for parole which are too complicated and require quite a long time to reach a decision to accept or reject the proposal, then family guarantor. The whereabouts of prisoners are unknown, and there are prisoners who violate disciplinary regulations in correctional institutions so that their right to parole is lost.